Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsaem.7b00343
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pseudocapacitive NiO Nanoflakes through Surfactant-Free Facile Microwave-Assisted Route

Abstract: A facile and rapid surfactant-free microwave-assisted route is developed to synthesize 10 nm sized NiO nanoflakes with high pseudocapacitive performance for supercapacitor cells. The NiO nanoflakes exhibit mesoporous channels and a surface area as high as 206 m 2 g −1 as revealed under BET study, while the structural identity verified by XRD and IR confirm the phase purity of NiO. NiO nanoflakes maintain ∼85% of their thermal stability at temperature 900 °C which can be related to strong intermolecular forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…The pore diameter and pore volume of SCM are found to be 4.67 nm and 0.041 cm 3 g À1 ,r espectively,w hich is likely to provide good electrode/electrolyte contact, high electrolyte accessibility,and excellent chargetransfer. [35] Av ery high value of diffusion coefficient (2.1 10 À9 cm 2 s À1 )i si ndicative of the effective accessibility of OH À ions into the SCM electrode. SCM voltammograms exhibit very high capacitance in KOH (690.4 Fg À1 )c ompared with KNO 3 (67.35 Fg À1 )a t5mV s À1 indicating that OH À ions are highly favorable for intercalationtype energy storage.T he cyclic voltammograms at different scan rates (Figure 4a)d isplay two redoxp eaks, confirming the pseudocapacitive behavior of SCM.T he charging and discharging characteristics shown in Figure 4b are noticeably deviated from isosceles triangular form andt hus exhibit pseudocapacitance.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The pore diameter and pore volume of SCM are found to be 4.67 nm and 0.041 cm 3 g À1 ,r espectively,w hich is likely to provide good electrode/electrolyte contact, high electrolyte accessibility,and excellent chargetransfer. [35] Av ery high value of diffusion coefficient (2.1 10 À9 cm 2 s À1 )i si ndicative of the effective accessibility of OH À ions into the SCM electrode. SCM voltammograms exhibit very high capacitance in KOH (690.4 Fg À1 )c ompared with KNO 3 (67.35 Fg À1 )a t5mV s À1 indicating that OH À ions are highly favorable for intercalationtype energy storage.T he cyclic voltammograms at different scan rates (Figure 4a)d isplay two redoxp eaks, confirming the pseudocapacitive behavior of SCM.T he charging and discharging characteristics shown in Figure 4b are noticeably deviated from isosceles triangular form andt hus exhibit pseudocapacitance.…”
Section: Resultsmentioning
confidence: 98%
“…The diffusion coefficient of OH À ions was also estimated through the Randle'sp lot ( Figure S10) by using previously reported procedures. [35] Av ery high value of diffusion coefficient (2.1 10 À9 cm 2 s À1 )i si ndicative of the effective accessibility of OH À ions into the SCM electrode. As shown in Figure 4c,t he specific capacitance (and specific capacity) calculated fromg alvanostaticc harge-discharge( GCD) curveso f SCM are 1223.34 Fg À1 (168.88 mAh g À1 )a t1Ag À1 ,9 09.09 Fg À1 (122.7 mAh g À1 )a t5Ag À1 ,a nd 665.12 Fg À1 (87.5 mAh g À1 )a t 10 Ag À1 .E vidently,S CM shows very good capacitance retention (> 50 %) at high current density.T he SCM electrode also www.chemsuschem.org exhibitede xcellent cycling stability and columbic efficiency (93.52 %c apacitance retention after 5000 charge-discharge cycles at 10 Ag À1 ;F igure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NiO material can exhibit pseudocapacitive behavior. For instance, the NiO nanoflakes synthesized through the microwave-assisted method displayed a high pseudocapacitive performance as electrode material for supercapacitor, as well as a high conductivity of 33.87 Scm −1 at room temperature, and surface area as high as 206 m 2 g −1 [238]. In another study, a Co-Ni/Co 3 O 4 -NiO nano-heterostructures demonstrated a remarkable pseudocapacitance [44].…”
Section: Nickel Oxide (Nio)mentioning
confidence: 97%
“…Among them, transition metal oxide based materials have been employed as electrode materials because they exhibit excellent pseudocapacitive behavior owing to their redox behavior arising from their surface functional groups, grain boundaries and crystal defects. Recently, various transition metal oxides such as V 2 O 5 , [34] MnO 2 , [35] NiO, [36] Co 3 O 4 , [37] Fe 2 O 3 , [38][39] Fe 3 O 4 , [40] and TiO 2 [41] and their composites have been studied for supercapacitor applications. Among them, Iron oxide is a promising candidate owing to its multiple oxidation states, high theoretical specific capacitance (3625 F g À 1 ), suitable potential window, abundance in nature, low cost and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%